2018
DOI: 10.15406/mojap.2018.05.00205
|View full text |Cite
|
Sign up to set email alerts
|

Embryo transfer, a potential risk in disease transmission

Abstract: Several studies have been performed to determine the disease transmission potential of early bovine embryos. Most of them agree that the Zona Pellucida (ZP) is a barrier that generally protects the embryo from infection but can also be a potential route for the transmission of pathogens. This review will initially focus on the characteristics of the ZP and the potential ways in which an embryo can transmit disease and the possible alternatives to reduce this hazard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…(BVDV), Bovine Leukemia Virus (BLV), Bovine Tuberculosis (TB), Brucellosis, etc.. It is stated that the zona pellucida (ZP) is an important barrier for infectious agents to infect the oocyte and embryo (Escobar 2018). However, ZP may permit the transmission of some diseases.…”
Section: Hereditary Transmitted Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…(BVDV), Bovine Leukemia Virus (BLV), Bovine Tuberculosis (TB), Brucellosis, etc.. It is stated that the zona pellucida (ZP) is an important barrier for infectious agents to infect the oocyte and embryo (Escobar 2018). However, ZP may permit the transmission of some diseases.…”
Section: Hereditary Transmitted Diseasesmentioning
confidence: 99%
“…Most of the transport of pathogens occurs by penetrating ZP. Therefore, embryos should be washed in Dulbecco's phosphate buffered saline (dPBS) at least 10 times before transfer or freezing procedures (Escobar 2018). Studies have reported that BVDV that has penetrated the ZP can be removed by washing (Gard et al 2009).…”
Section: Hereditary Transmitted Diseasesmentioning
confidence: 99%
See 1 more Smart Citation